(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This article discusses the political relations of the Ashtarkhanid dynasty, particularly with Russia, India, Iran, and Turkey, in the Bukhara Khanate from the early 17th century to the second half of the 18th century. During this period, the Bukhara Khanate maintained mutual economic, political, cultural, and diplomatic relations with neighboring states, including the exchange of ambassadors. This article focuses on the foreign relations of the Ashtarkhanid period.